1997
DOI: 10.1038/386852a0
|View full text |Cite
|
Sign up to set email alerts
|

An achaete-scute homologue essential for neuroendocrine differentiation in the lung

Abstract: In Drosophila and in vertebrates, the achaete-scute family of basic helix-loop-helix transcription factors plays a critical developmental role in neuronal commitment and differentiation. Relatively little is known, however, about the transcriptional control of neural features in cells outside a neuronal context. A minority of normal bronchial epithelial cells and many lung cancers, especially small-cell lung cancer, exhibit a neuroendocrine phenotype that may reflect a common precursor cell population. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
385
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(397 citation statements)
references
References 18 publications
10
385
0
2
Order By: Relevance
“…However, both of these two hASH1 þ adenocarcinomas also expressed neuroendocrine markers. Thus, our data confirmed and extended the findings of previous in vitro studies that hASH1 was specifically expressed in lung cancers with neuroendocrine differentiation, 12,14,18,19 indicating that besides being instrumental in development of a subset of neurons and neuroendocrine cells, 8,[13][14][15][16][17] hASH1 also plays a key role in regulating neuroendocrine differentiation of tumor cells. The term 'neuroendocrine differentiation' in a broad sense is used to define cells expressing a neural and/or an endocrine phenotype.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, both of these two hASH1 þ adenocarcinomas also expressed neuroendocrine markers. Thus, our data confirmed and extended the findings of previous in vitro studies that hASH1 was specifically expressed in lung cancers with neuroendocrine differentiation, 12,14,18,19 indicating that besides being instrumental in development of a subset of neurons and neuroendocrine cells, 8,[13][14][15][16][17] hASH1 also plays a key role in regulating neuroendocrine differentiation of tumor cells. The term 'neuroendocrine differentiation' in a broad sense is used to define cells expressing a neural and/or an endocrine phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…This work was supported by Grants from the Ministry of Education, Culture, Sports, Science and Technology (15590314 and High-tech research center) and from the Ministry of Health, Labor and Welfare (11)(12)(13)(14)(15)(16)(17)(18)(19) 2002), Japan…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in some cases, the development of distant metastases occurred many years after surgery and subsequent chemotherapy, suggesting that the different tumor cell populations, exocrine (mucinous), and neuroendocrine may play complex reciprocal interactions. In this respect, the expression of transcription factors known to drive neuroendocrine differentiation in the embryonic life, such as human achaete-scute-homologue type 1 (hASH1) may be involved in the occurrence of neuroendocrine differentiation [16]. Unfortunately, in the present series, no hASH1 expression was observed (data not shown) suggesting that at least in the intestinal area, the development of neuroendocrine differentiated cells may follow alternative pathways, compared to other models such as the prostate [17].…”
Section: Discussionmentioning
confidence: 99%
“…18 mASH1 is required at an early stage in neuronal differentiation and initiates a differentiation program involving NeuroD. 19 It is reported that hASH1 is expressed selectively in normal fetal pulmonary neuroendocrine cells 20 as well as in pulmonary large cell neuroendocrine carcinoma (56.7%) and small cell carcinoma (71.8%). 21 The frequency of expression of mASH1 in our study was 59% in large cell neuroendocrine carcinoma and 87% in small cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%